The Effect of Content Marketing on Purchase Intention through Brand Trust as a Mediating Variable in Gen Z Skincare Users - Abdul Ilham Subarkah; Kokom Komariah; Sopyan Saori (Dinasti Publisher, 2025)
Content marketing has become one of the alternative strategies to increase business value, particularly in building long-term relationships with consumers. Strong brand trust plays an essential role in the success of content marketing and leads to the emergence of consumer purchase intention. This study aims to determine whether content marketing influences purchase intention through brand trust as a mediating variable in skincare product The Originote in Sukabumi City. This research uses a quantitative method with a descriptive approach. The population consists of Gen Z individuals aged 14–28 years who use The Originote skincare products in Sukabumi City. The sample includes 200 respondents, and the data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS version 3. The results show that content marketing has a significant effect on brand trust, brand trust has a significant effect on purchase intention, content marketing significantly affects purchase intention, and brand trust can mediate the relationship between content marketing and purchase intention. This indicates that brand trust is able to mediate the relationship between content marketing and purchase intention among The Originote consumers in Sukabumi City.